Comparing life history traits and tolerance to changing environments of two oyster species (Ostrea edulis and Crassostrea gigas) through Dynamic Energy Budget theory. Issue 1 (8th July 2022) - Stechele, Brecht; Maar, Marie; Wijsman, Jeroen; Van der Zande, Dimitry; Degraer, Steven; Bossier, Peter; Nevejan, Nancy
Abstract : European flat oysters ( Ostrea edulis ) and Pacific cupped oyster ( Crassostrea gigas ) have distinct differences in Dynamic Energy Budget parameters. These parameters explain their history traits and life strategies when exposed to changing environments in Northern Europe. Abstract: To predict the response of the European flat oyster ( Ostrea edulis ) and Pacific cupped oyster ( Crassostrea gigas/Magallana gigas ) populations to environmental changes, it is key to understand their life history traits. The Dynamic Energy Budget (DEB) theory is a mechanistic framework that enables the quantification of the bioenergetics of development, growth and reproduction from fertilization to death across different life stages. This study estimates the DEB parameters for the European flat oyster, based on a comprehensive dataset, while DEB parameters for the Pacific cupped oyster were extracted from the literature. The DEB parameters for both species were validated using growth rates from laboratory experiments at several constant temperatures and food levels as well as with collected aquaculture data from the Limfjorden, Denmark, and the German Bight. DEB parameters and the Arrhenius temperature parameters were compared to get insight in the life history traits of both species. It is expected that increasing water temperatures due to climate change will be beneficial for both species. Lower assimilation rates and high energy allocation to soma explain O. edulis' slow growth and low reproductive output. Crassostrea gigas' high assimilation rate, low investment in soma and extremely low reserve mobility explains the species' fast growth, high tolerance to starvation and high reproductive output. Hence, the reproductive strategies of both species are considerably different. Flat oysters are especially susceptible to unfavourable environmental conditions during the brooding period, while Pacific oysters' large investment in reproduction make it well adapted to highly diverse environments. Based on the life history traits, aquaculture and restoration of O. edulis should be executed in environments with suitable and stable conditions.